The search for failed supernovae with the Large Binocular Telescope: a new candidate and the failed SN fraction with 11 yr of data. Issue 1 (13th September 2021) - Neustadt, J M M; Kochanek, C S; Stanek, K Z; Basinger, C; Jayasinghe, T; Garling, C T; Adams, S M; Gerke, J
ABSTRACT: We present updated results of the Large Binocular Telescope Search for Failed Supernovae. This search monitors luminous stars in 27 nearby galaxies with a current baseline of 11 yr of data. We re-discover the failed supernova (SN) candidate N6946-BH1 as well as a new candidate, M101-OC1. M101-OC1 is a blue supergiant that rapidly disappears in optical wavelengths with no evidence for significant obscuration by warm dust. While we consider other options, a good explanation for the fading of M101-OC1 is a failed SN, but follow-up observations are needed to confirm this. Assuming only one clearly detected failed SN, we find a failed SN fraction f = 0.16^+0.23_-0.12 at 90 per cent confidence. We also report on a collection of stars that show slow (∼decade), large amplitude (Δ L / L > 3) luminosity changes.